Analisis Laju Korosi Proses Pelapisan Pada Plat Dinding Kereta Di Balai Yasa SGU (Politeknik Perkeretaapian Indonesia Madiun, 2023)
Corrosion is the process of material damage that occurs due to the surrounding environment. One way to control corrosion of metal is by coating the surface of the carriage wall consisting of anti-rust paint (epoxy), putty, and color paint. This study aims to determine the effect of coating treatment and the effect of initial treatment on the corrosion rate with the salt mist test. Coating is one method that can inhibit corrosion of metal materials. The salt mist method is used to determine the level of resistance of metal materials to corrosion under certain conditions according to the ASTM B117 standard. Weight loss is one of the methods to determine the corrosion rate by calculating the difference between the weight of the specimen before the test and the specimen after the test. From this test, information will be obtained on the effectiveness of the coating in restraining the corrosion rate. From the test results, it was found that the initial wetblasting treatment with coating and wetblasting without coating had the highest corrosion rates of 0.00054 mmpy and 0.2190 mmpy. While the results of the initial treatment of sandpaper with coating and sandpaper without coating were lower, namely 0.000274 mmpy and 0.00192 mmpy. From the calculation results, it can be concluded that the sandpaper treatment is better than the wetblasting treatment in overcoming the corrosion rate of the galvanized material.